Real-time air pollution and bipolar disorder symptoms: remote-monitored cross-sectional study - Aaron Kandola; Joseph F. Hayes (BJPsych Open, 2023)
Air pollution is associated with unipolar depression and other mental health problems. We assessed the real-time association between localised mean air quality index and the severity of depression and mania symptoms in people with bipolar disorder. We found that as air quality worsened, symptoms of depression increased. We found no association between air quality and mania symptoms.